Organizational Ownership Patterns and Efficiency: A Case Study of Private and Cooperative Sugar Factories in South India - Ghorpade, Jai (Academy of Management Journal, 1973)
This study investigated the relative organizational efficiency of two types of organizational systems currently competing for resources and political patronage in India. The samples consisted of 26 joint stock companies and 17 cooperatives. Statistical analysis failed to reveal any significant differences in efficiency levels of the two organizational groups.